Factors Affecting the Dietary Diversity Pattern of Women and Children in Rural Areas of Southern Punjab: A Case of District Vehari - Sajjad, Asma; Mansha, Muhammad; Sarwar, Kiran; Siddique, Haris Ali (iRASD Journal of Economics, 2022)
The purpose of this study was to examine the factors that affect rural mothers’ and children’s dietary diversity patterns in Southern Punjab, district Vehari. Children and Women Dietary Diversity Pattern (CDDP & WDDP) illustrate how economically capable women and children are to acquire a wide range of foods. CDDP & WDDP are multi-dimensional. Various socioeconomic factors can affect CDDP & WDDP. The Primary data has been collected from 300 children and 300 women from rural areas. A detailed questionnaire was created to gather information from the respondents following the FAO’s recommendations. The data analysis method employed was ordered logistic regression. The findings of this study suggest that children in rural regions’ estimated coefficients of child’s age, mother’s age, maternal education, the income of the household, land, area, and livestock do a have positive impact on children’s dietary diversity scores and statistically signify.